Characterisation of Fragaria vesca fruit from Italy following a metabolomics approach through integrated mass spectrometry techniques. (December 2016) - D'Urso, Gilda; Maldini, Mariateresa; Pintore, Giorgio; d'Aquino, Luigi; Montoro, Paola; Pizza, Cosimo
Abstract: The phytochemical content of Fragaria vesca L. (wild strawberry) grown in Campania Region (South Italy) was investigated. Wild and cultivated fruit were collected from different geographic areas and from bothautochthonous and non-autochthonous germplasm. Extracts were submitted to untargeted liquid chromatography coupled to high resolution mass spectrometry (LC–ESI-Orbitrap–MS) for metabolite profiling. 39 different phenolic compounds have been detected and identified in the methanolic extract of spontaneous and cultivated strawberries from different origins. Targeted quantitative analyses of selected known metabolites were performed using UHPLC interfaced to Q-Trap mass spectrometer in Multiple Reaction Monitoring mode. Principal Component Analysis (PCA) was applied to both untargeted and targeted results. PCA was applied to the untargeted profiling data indicating that fruits from locations with different pedoclimatic conditions can be discerned. Results from quantitative analysis indicate that autochthonous strawberries display significantly higher levels of anthocyanins, especially cyanidin 3- O -glucoside, and other phenolic compounds, like gallic acid and procyanidin B1, compared to the one from non-autochthonous germplasm. The targeted and untargeted metabolite profiling approach used in this work is proposed for the assessment of geographical origin of the berries. Highlights: MS based Metabolomics can help in the assessment of berry's geographical origin. 39 polyphenolic compounds were identified in Fragaria vesca fruit by High Resolution MS. Quantification of selected marker compounds in different samples highlighted variability. Spontaneous strawberries produced higher amount of anthocyanins.